Trust and trustworthy computing : 9th International Conference, TRUST 2016, Vienna, Austria, August 29-30, 2016, Proceedings /: 9th International Conference, TRUST 2016, Vienna, Austria, August 29-30, 2016, Proceedings. (2016) - Unknown
No abstract available